From Transparency to Trust: The Impact of ESG Disclosure on the Reputation of Coal Companies in Indonesia - Mukholifah, Egma; Khafid, Muhammad (STIE Pelita Nusantara Semarang, 2026)
ESG disclosure has become a critical element for companies seeking to build credibility and strengthen their reputation, particularly in the coal industry, which faces heightened environmental and social scrutiny. This study provides empirical evidence on the effect of ESG disclosure on the corporate reputation of coal companies in Indonesia and examines the moderating role of firm size. A quantitative approach was employed using unbalanced panel data comprising coal companies listed on the Indonesia Stock Exchange for the period 2022–2024, resulting in 124 units of analysis. ESG disclosure was measured through economic, environmental, and social performance indicators, while corporate reputation was proxied by market reactions surrounding the publication dates of annual and sustainability reports. The analysis was conducted using Moderated Regression Analysis (MRA) with a Common Effect Model. The findings reveal that economic and environmental performance disclosures positively and significantly influence corporate reputation, whereas social performance disclosure shows no significant effect. Moreover, firm size weakens the influence of economic and environmental disclosures on reputation and fails to strengthen the effect of social disclosure. These results indicate that economic and environmental transparency play an essential role in shaping the reputation of coal companies, although their effectiveness may diminish for larger firms. This study contributes to the development of more effective ESG disclosure strategies within the mining sector.